SUNDANESE TRADITIONAL GAMES AS MEDIA FOR PROMOTING CHILDREN’S COGNITIVE, AFFECTIVE AND PSYCHOMOTOR DEVELOPMENT IN CIKAUM SUBANG - Atri Nadia Astarina; Ida Zuraida; Hendar; Heri Heryono; Meita L. Sujatna (Lembaga Penelitian Universitas Pasundan, 2023)
Preschool age that ranges from three to five years old is considered as a critical period for children’s development in several aspects. This development is highly suggested to be stimulated through activities that can be enjoyed by the children. Starting from this point, this study aims to investigate how Sundanese traditional games can promote the development of children’s cognitive, affective, and psychomotor abilities that are widely recognized as the three crucial learning domains proposed by Bloom (1956). The study that was conducted in Early Childhood Education (PAUD) in Cikaum Subang employed a descriptive qualitative method. The data of this study were taken from questionnaires that were distributed to 92 PAUD teachers as the participants. The study reveals that about 85% of the participants implemented traditional games as one of the teaching methods in their classes. Based on the analysis, it was found that the various types of traditional games employed by singing, guessing riddles, doing role play, and involving physical activities could promote the development of children’s cognitive, affective, and psychomotor capacities in three main ways. First, they provided children with game activities that could stimulate their thinking, counting, remembering, and solving problems capacity. Second, they helped develop children’s emotional quotient through the values learned and rules implemented in the games. Lastly, they involved physical activities that could improve the children’s strength, durability, flexibility,and balance.